Hexasodium fytate exposure-response correlations in a randomized, placebo-controlled study of patients on dialysis with cardiovascular calcification - Perelló, Joan; Alberti, Joan; Torres, Juan Vicente; Ferrer, Miguel D.; Perez, M. Mar; Bassissi, Firas; Gold, Alex; Raggi, Paolo; Chertow, Glenn M.; Salcedo, Carolina (Frontiers in Pharmacology, 2024)
Background. Patients receiving dialysis have high cardiovascular risk in part due to extensive vascular calcification. In the CaLIPSO study, infusion of hexasodium fytate (SNF472), the hexasodium salt of inositol hexaphosphate, for 52 weeks thrice weekly during hemodialysis significantly reduced progression of coronary artery calcification (CAC). This report examines pharmacokinetic/pharmacodynamic (PK/PD) and exposure-efficacy in CaLIPSO. Methods. We measured hexasodium fytate plasma concentrations (PK) by validated liquid chromatography-mass spectroscopy, and hydroxyapatite crystallization in plasma (PD) by validated spectrophotometry. Analyses included patients evaluable for PK, PD, and CAC change (per-protocol analysis). We developed a simple Emax model for maximum concentration (Cmax) and PD effect, and linear and non-linear Emax models for exposure-efficacy among individual average Cmax and absolute and percent changes in CAC score from baseline to week 52. Results. Among evaluable patients receiving placebo (n=15), 300 mg (n=20), or 600 mg (n=20), average Cmax across visits was not quantifiable (<0.76 μM), 15 µM, and 46 µM, respectively. These results suggest a more-than-proportional increase, without accumulation, with a Cmax ratio of approximately 3 for the doses administered. Average inhibition of hydroxyapatite crystallization was 15%, 61%, and 75%, respectively, and similar across visits. Simple Emax models described 80% maximal effect at exposures >21.9 µM and a plateau in exposure-efficacy above the third quartile of Cmax (≥32 µM). Conclusions. Hexasodium fytate has exposure-dependent effects on hydroxyapatite crystallization and progression of cardiovascular calcification. Simple Emax models show robust relations among exposure, inhibition of hydroxyapatite crystallization, and change in CAC volume.